2011
DOI: 10.1083/jcb.201011061
|View full text |Cite
|
Sign up to set email alerts
|

The yeast Cbk1 kinase regulates mRNA localization via the mRNA-binding protein Ssd1

Abstract: In the absence of Cbk1 phosphorylation Ssd1-associated mRNAs are redirected from sites of polarized cell growth to stress granules and P-bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
130
0
5

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(142 citation statements)
references
References 61 publications
(152 reference statements)
7
130
0
5
Order By: Relevance
“…In brief, Ssd1 is an RNAseII-related protein broadly conserved in fungi that appears to lack catalytic activity; it has been implicated in numerous processes. It binds specific mRNAs and suppresses their translation, and Cbk1 efficiently directly negatively regulates this Ssd1 function in vivo (Hogan et al 2008;Jansen et al 2009;Kurischko et al 2011a). This is critical for cell wall remodeling during bud growth; however, the Ssd1 translational control system's important role in cell morphogenesis outside of the process of mother/ daughter separation is not discussed further in this chapter.…”
Section: Ram Network Controls Translation Of Cell Separation Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, Ssd1 is an RNAseII-related protein broadly conserved in fungi that appears to lack catalytic activity; it has been implicated in numerous processes. It binds specific mRNAs and suppresses their translation, and Cbk1 efficiently directly negatively regulates this Ssd1 function in vivo (Hogan et al 2008;Jansen et al 2009;Kurischko et al 2011a). This is critical for cell wall remodeling during bud growth; however, the Ssd1 translational control system's important role in cell morphogenesis outside of the process of mother/ daughter separation is not discussed further in this chapter.…”
Section: Ram Network Controls Translation Of Cell Separation Proteinsmentioning
confidence: 99%
“…Ssd1 likely assembles a translationally silent mRNP in the nucleus: it associates with unspliced and centromeric mRNAs, interacts with the phosphorylated Cterminal tail of RNA polymerase II, and requires a sequence that can function as an NLS (Phatnani et al 2004;Jansen et al 2006;Hogan et al 2008;Kurischko et al 2011b). The mechanisms and precise function of Ssd1's control of translation remain poorly understood, but since RAM network proteins concentrate at the bud neck during cell separation, the Ssd1 circuit could allow the cytokinesis site to exert posttranscriptional control over the expression of proteins needed at different stages of the process (Nelson et al 2003;Jansen et al 2006;Kurischko et al 2011a).…”
Section: Ram Network Controls Translation Of Cell Separation Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting RNA transcripts are also subject to further regulation at the levels of RNA processing, transport, localization, translation, and degradation. The added dimensions of regulation provided by RNAbinding proteins (RBPs) enable more precise temporal, spatial, and stoichiometric control of protein production (Wang et al 2002;Paquin et al 2007;Jansen et al 2009;Kurischko et al 2011). Specific RBPs bind to distinct sets of mRNAs, typically encoding proteins destined for similar subcellular localizations or with related biological functions, suggesting a model in which concerted, combinatorial binding of specific mRNAs by specific sets of RBPs can affect the post-transcriptional fate of potentially every mRNA in the cell (Hieronymus and Silver 2003;Gerber et al 2004;Ong et al 2004;Keene 2007a,b;Hogan et al 2008).…”
mentioning
confidence: 99%
“…We have previously found that a multicopy SSD1 encoding an RNA-binding protein suppressed the growth defect caused by the ccr4⌬ khd1⌬ double mutation (16). Since the RNA-binding protein Ssd1 is involved in the regulation of many genes as well as Khd1 (17,34,35), the Pbp1 and Rpl12 proteins may also involve the expression of multiple genes in a negative effect on cell growth in the ccr4⌬ khd1⌬ double mutant cells. Since Rpl12a and Rpl12b stabilize the structure of the P-protein stalk by interacting with the P0/P1/P2 complex (32,33), the rpl12a⌬ and rpl12b⌬ mutations as well as the pbp1⌬ mutation decrease the translation of multiple target mRNAs that influence cell growth.…”
Section: Discussionmentioning
confidence: 99%